VD_FINDINFO AI 85/09 - 311/2009 vom 21. Oktober 2009 - VD Tribunal cantonal (2009)
FAITS NOUVEAUX, RADIATION DU RÔLE | 56 al. 1 LPGA, 58 al. 1 LPGA, 60 al. 1 LPGA, 61 let. g LPGA, 2 LPA-VD, 49 LPA-VD, 55 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. c LPA-VD, 98 LPA-VD